Time in Miguel de Unamuno’s "Paz en la guerra" and "Niebla" - Bergeson, Craig (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
Although many readers of Unamuno’s novels have noted that the style of his first novel, “Paz en la guerra” (1897), is quite traditional and that, therefore, it differs considerably from the style of the novels he will write later, it also contains elements that clearly link it to his subsequent novels. One of these is the manipulation of time, which detains time and produces what Henri Bergson would call the “virtualization” of time. Time is also detained and virtualized in other Unamuno novels—in particular, “Niebla.” For example, in “Niebla” various temporal anomalies reveal Unamuno’s desire to detain time and eternalize the moment in order to escape death and exist perpetually, a desire also present in “Paz en la guerra.” The present study therefore shows that through its particular manipulation of time, “Paz en la Guerra” is clearly linked to Unamuno’s more experimental novels.